Trichoderma composting of Banana peel. - Licup, Ana Theresa D.
Banana peels of "Saba" (Musa paradisiaca) were composted with the help of Tricoderma. The process of decomposition was monitored by noting changes in temperature, odor, and substrate consistency. Composted peels were later analyzed for N, P, K, Ca, Mg, total carbon content, pH, and organic matter content. The average composting period was 28.4 days and the compost contained 2.21 nitrogen (N), 1.38 P2O5, and 6.07 K2O with an average pH of 7.6. A comparison of the chemical properties of banana peel compost with other agricultural by-products using Trichoderma shows the former to contain much higher amount of the substance being tested for. (NOTE: CORRECTION P2O5, K2O)